KAJIAN HUKUM TERHADAP PERTIMBANGAN HAKIM DALAM PUTUSAN BEBAS PERKARA PEMBUNUHAN BERENCANA (STUDI PUTUSAN NOMOR 120/Pid.B/2024/PN.Skh) - Laila Nur Rahmadiyah; Hanuring ayu; Firstnandiar Glica Aini (Verstek, 2026)
The purpose of this paper is to analyze the legal basis for the Panel of Judges' decision and acquittal in the criminal case of Decision Number 120/Pid.B/2024/PN.Skh. The research employed in this paper is normative legal research. The approaches employed in this study are the statutory approach, the case approach, and the conceptual approach. The Panel of Judges in Case Number 120/Pid.B/2024/PN.Skh issued an acquittal because the elements of premeditated murder, particularly the elements of intent and planning, were not legally and convincingly proven based on the evidence presented by the public prosecutor. Furthermore, the failure to fulfill the evidentiary requirements as stipulated in Article 183 of the Criminal Procedure Code (KUHAP) raised doubts among the judges, who then decided in favor of the defendant in accordance with the principle of in dubio pro reo. The acquittal verdict in Case Number 120/Pid.B/2024/PN.Skh complies with the principles of criminal law, particularly the principles of legality, the presumption of innocence, negative statutory proof, and in dubio pro reo. The panel of judges rendered the acquittal because the elements of premeditated murder were not legally and convincingly proven and were not supported by sufficient evidence, as stipulated in Article 183 of the Criminal Procedure Code. Given the doubts in the evidence, the judge is obligated to rule in the defendant's favor as a manifestation of justice and legal certainty.